Employment impacts of agrifood system innovations and policies: A review of the evidence - Berdegué, Julio A.; Trivelli, Carolina; Vos, Rob (Elsevier, 2025)
The agrifood sector (AFS) constitutes about one-sixth of the global economy and is the world's largest source of employment, supporting the livelihoods of most of the world’s poor and vulnerable people (Corong et al., 2024; Yi et al., 2024). In recent decades, global agricultural productivity has increased due to technological and institutional innovations. This has contributed to poverty reduction and improved food security. Despite these positive contributions, however, poverty remains widespread among rural and agrifood sector producers and workers. The challenge remains to address the constraints these producers and workers face and also enable more inclusive value chain development that would provide decent livelihoods and employment for those currently left behind. To this end, the CGIAR Initiative “Rethinking Food Markets and Value Chains for Inclusion and Sustainability” commissioned a meta study to identify knowledge gaps regarding the impacts of developing countries' agrifood value chain (AVC) integration and modernization processes on employment and income sharing (Berdegué et al., 2023). This paper summarizes its key findings and draws conclusions for further research.